2021
DOI: 10.1017/jfm.2020.900
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure inside and around a rectangular array of rigid emerged cylinders located at the sidewall of an open channel

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 71 publications
2
23
0
Order By: Relevance
“…see Kirkil & Constantinescu 2009, 2015; Chang et al. 2011, 2013; Chang, Constantinescu & Tsai 2017, 2020; Zeng & Constantinescu 2017; Koken & Constantinescu 2020). These studies have shown that for steady incoming flow conditions, DES can accurately predict the wake structure and dynamics of the shed billow vortices, the dynamics of the main horseshoe vortices and their interactions with the vortex tubes shed in the separated shear layers.…”
Section: Numerical Model Boundary Conditions and Test Casesmentioning
confidence: 99%
“…see Kirkil & Constantinescu 2009, 2015; Chang et al. 2011, 2013; Chang, Constantinescu & Tsai 2017, 2020; Zeng & Constantinescu 2017; Koken & Constantinescu 2020). These studies have shown that for steady incoming flow conditions, DES can accurately predict the wake structure and dynamics of the shed billow vortices, the dynamics of the main horseshoe vortices and their interactions with the vortex tubes shed in the separated shear layers.…”
Section: Numerical Model Boundary Conditions and Test Casesmentioning
confidence: 99%
“…see White & Nepf 2007; Zong & Nepf 2011, 2012; Chen et al. 2012; Chang, Constantinescu & Tsai 2017; Koken & Constantinescu 2020). These studies considered either a circular or rectangular patch positioned at the centre of a straight channel, or a long rectangular patch placed at one of the channel's banks.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of the vertical shear layer is constrained by the free surface, especially for low submergence cases, while the development of the horizontal shear layer vortices is constrained by bed friction effects at large distances from the origin of the shear layer (Finnigan 2000; Sukhodolova & Sukhodolov 2012 a ; Cheng & Constantinescu 2020). Although the structure of the flow inside the horizontal shear layer was studied experimentally (White & Nepf 2007) and numerically (Koken & Constantinescu 2020) for emerged rectangular arrays, no such information is available for submerged arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the nature of turbulent flow in vegetation is important in forestry, hydrology and agriculture. The relevance of scientific research to study the features of the formation and development of flow inside and near group structures of streamlined bodies is due to the search for more sustainable methods of environmental management, improvement of ecology and the use of natural resources, the development of weather and climate forecasting systems, as well as the need to study global biogeochemical cycles ( Lopes et al., 2015 ; Brunet, 2020 ; Koken and Constantinescu, 2021 ). For example, in channel streams, areas of vegetation improve water quality and habitat for fish.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have been carried out on the research of vortex and jet flows between single and group structures of bluff bodies and junction flows, both by numerical and experimental methods. RANS, DNS, LES and DES methods with various turbulence models k-ε, k-ω, k-g, SSD and others were used for numerical simulations ( Duraisamy et al., 2019 ; Rona et al., 2020 ; Chang et al., 2020 ; Chen et al., 2020a , 2020b ; Monti et al., 2020 ; Robison et al., 2021 ; Koken and Constantinescu, 2021 ; Hassan and Jalal, 2021 ; Zhao et al., 2022 ). Experimental studies of the fields of velocity, pressure, temperature and other parameters were carried out using a wide variety of sensors, measuring systems and equipment for recording, processing and analyzing data ( Bateni et al., 2019 ; Gautam et al., 2019 ; Galan et al., 2019 ; Hamed et al., 2019 ; Priyanka et al., 2019 ; Guan et al., 2019 ; Karimaei and Zarrati, 2019 ; Zuccarello et al., 2020 ; Yang et al., 2020 , 2021 ).…”
Section: Introductionmentioning
confidence: 99%